Research on the Fair Use of Re-created Short Videos - Zhao, Canyang (International Journal of Social Sciences and Public Administration, 2025)
With the advent of the vigorous development of science and technology, the national short video creation boom has swept in. While the secondary creation of short videos has become a new trend in video creation, it is also facing the risk of copyright infringement. How to establish a balance of interests mechanism between copyright owners and the public, especially secondary short video creators, is the research direction of the fair use system. The fair use system can ensure that copyright is not infringed within a reasonable range, and promote the reasonable use, innovation, dissemination and promotion of the original work by the secondary creation of short videos. The creation of secondary short video creators within the scope of the fair use system can not only expand the influence of the original work, but also enrich the atmosphere of video creation and improve the vitality of video creation.